Randomized comparison trial of density and context of upper limb intensive group versus individualized occupational therapy for children with unilateral cerebral palsy. (27th January 2015) - Sakzewski, Leanne; Miller, Laura; Ziviani, Jenny; Abbott, David F; Rose, Stephen; Macdonell, Richard A L; Boyd, Roslyn N
<x xml:space="preserve">Abstract</x> Aim To determine whether short‐term intensive group‐based therapy combining modified constraint‐induced movement therapy and bimanual therapy (hybrid‐CIMT) is more effective than an equal total dose of distributed individualized occupational therapy (standard care) on upper limb motor and individualized outcomes. Method Fifty‐three children with unilateral cerebral palsy (69% males; mean age 7y 10mo, SD 2y 4mo; Manual Ability Classification System level I, n=24; level II, n=23) were randomly allocated, and 44 received either hybrid‐CIMT (n=25) or standard care (n=19). Standard care comprised six weekly occupational therapy sessions and a 12‐week home programme. Outcomes were assessed at baseline, 13 weeks, and 26 weeks after treatment. Results Groups were equivalent at baseline. Standard care achieved greater gains on satisfaction with occupational performance after intervention (estimated mean difference −1.2, 95% CI −2.2 to −0.1; p=0.04) and Assisting Hand Assessment at 26 weeks (estimated mean difference 3.1, 95% CI 0.2–6.0; p=0.04). Both groups demonstrated significant improvements in dexterity of the impaired upper limb, and bimanual and occupational performance over time. The differences between groups were not clinically meaningful. Interpretation There were no differences between the two models of therapy delivery. Group‐based intensive camps may not be readily available; however, individualized standard care augmented with a home programme may offer an effective alternative but needs to be provided at a sufficient dose.